2017
DOI: 10.1160/th17-03-0156
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Receptor Expressed on Myeloid cells-1: a new player in platelet aggregation

Abstract: Triggering Receptor Expressed on Myeloid cells-1 (TREM-1) is an immunoreceptor initially known to be expressed on neutrophils and monocytes/macrophages. TREM-1 acts as an amplifier of the inflammatory response during both infectious and aseptic inflammatory diseases. Another member of the TREM family, The Triggering receptor expressed on myeloid cells Like Transcript-1 (TLT-1) is exclusively expressed in platelets and promotes platelet aggregation. As the gene that encodes for TLT-1 is located in the TREM-1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Taken together, our findings of an elevated plasma sTREM-1 level in patients with thrombotic PAPS and its correlation with elevated levels of ESR and serum hsCRP suggest that thrombotic APS is characterized by TLR-4-mediated innate immune activation [3436] and possibly platelet activation [46]. Moreover, the correlation of elevated plasma sTREM-1 with venous and arterial thrombotic events suggests that plasma sTREM-1 can be used as a biomarker of thrombosis during follow-up of patients with PAPS.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Taken together, our findings of an elevated plasma sTREM-1 level in patients with thrombotic PAPS and its correlation with elevated levels of ESR and serum hsCRP suggest that thrombotic APS is characterized by TLR-4-mediated innate immune activation [3436] and possibly platelet activation [46]. Moreover, the correlation of elevated plasma sTREM-1 with venous and arterial thrombotic events suggests that plasma sTREM-1 can be used as a biomarker of thrombosis during follow-up of patients with PAPS.…”
Section: Resultsmentioning
confidence: 87%
“…Another potential role for TREM-1 in thrombotic APS was suggested by recent data showing that TREM-1 is constitutively expressed in platelet α-granules and which, upon platelet activation, is mobilized to the platelet surface [46]. Pharmacologic inhibition of TREM-1 in platelets from humans and also from trem-1 −/− mice reduced both the platelet activation as well as the platelet aggregation induced by collagen, adenosine diphosphate, and thrombin [46]. Moreover, in vivo TREM-1 inhibition decreased thrombus formation in a carotid artery model of thrombosis and protected mice during pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, inhibition of TREM‐1 depresses thrombus formation in a carotid artery model and protects mice during pulmonary embolism, without excessive bleeding 15. Platelet plays a pivotal role in chronic inflammation, leading to development and progression of atherosclerosis and acute coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have found that TREM‐1 and its signaling pathways also lead to several acute and chronic noninfectious inflammatory diseases, including atherosclerosis, colitis, fibrosis, and cancer 14. Furthermore, TREM‐1 is constitutively expressed in a‐granules and mobilized at the membrane on platelet activation 15. sTREM‐1, a soluble form of TREM‐1 shed from the membrane of activated phagocytes, used to be identified as a marker to distinguish infectious from noninfectious inflammatory states, and its significance in infectious diseases is clearly confirmed 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…TLT-1 is a type-1 transmembrane protein [5,6,9] that is highly and exclusively expressed in megakaryocytes and platelets [10], stored in α-granules and possibly in another platelet compartment, and is rapidly upregulated on the surface of activated platelets, with CD62P showing the most obvious increase in expression [11]. Upon platelet activation, TLT-1 is transported to the membrane, where it enhances Ca2+ influx and promotes platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%